2010
DOI: 10.1111/j.1440-0960.2010.00664.x
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 and type IV hypersensitivity to nickel

Abstract: We report a case of type 1 and type IV contact hypersensitivity to nickel. Very few cases of immediate contact urticaria to nickel have been reported. The mechanism behind this is not fully understood, although it has been postulated that nickel may act as a mast cell discharger on a non-immunological basis. Nickel is found in varying concentrations in stainless steels; its biological availability varies depending on the alloy composition. Our patient has adapted her lifestyle to minimize her contact with hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 6 publications
3
20
0
Order By: Relevance
“…The rougher surface and larger surface area tend to have more corrosion than smoother and smaller surface area. The surface corrosion of NiTi alloy could release nickel ion that can evoke allergic reactions [26] in contacting tissues. In this sense, HF treatment which resulted in smoother surface in this experiment is postulated to contribute to increasing the cyclic fatigue resistance of NiTi files as well as lowering the corrosion tendency of them.…”
Section: Discussionmentioning
confidence: 99%
“…The rougher surface and larger surface area tend to have more corrosion than smoother and smaller surface area. The surface corrosion of NiTi alloy could release nickel ion that can evoke allergic reactions [26] in contacting tissues. In this sense, HF treatment which resulted in smoother surface in this experiment is postulated to contribute to increasing the cyclic fatigue resistance of NiTi files as well as lowering the corrosion tendency of them.…”
Section: Discussionmentioning
confidence: 99%
“…These usually consisted of vesicular hand eczema or systemic contact dermatitis . Very few cases of immediate and delayed hypersensitivity, presenting mostly with contact urticaria, have been reported . Finally, a patient with a systemic nickel allergy presenting as papuloerythroderma‐like eruptions was described .…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Very few cases of immediate and delayed hypersensitivity, presenting mostly with contact urticaria, have been reported. 5 Finally, a patient with a systemic nickel allergy presenting as papuloerythroderma-like eruptions was described. 9 This case benefited from a nickel-free diet and the removal of dental braces was not necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Indeed, it has been demonstrated that Th1 and Th2 reactions are not mutually exclusive and can occur concurrently in atopic patients. 23 Thus, it is notable that nickel, which consistently tops the list of clinically relevant allergens in multiple studies, 9,15,16 is not only capable of inducing both type I and type IV hypersensitivity reactions, 24 but has also been shown to induce higher rates of contact allergy in those with lossof-function filaggrin gene mutations, commonly seen in atopic patients. 25 More than one study has demonstrated that the rate of contact Th1 and Th2 reactions are not mutually exclusive and can occur concurrently in atopic patients.…”
Section: Special Considerations For Acd and Admentioning
confidence: 99%